An updated comprehensive systematic review of Cladophialophora bantiana and analysis of epidemiology, clinical characteristics, and outcome of cerebral cases. (22nd December 2016) - Kantarcioglu, A. Serda; Guarro, Josep; De Hoog, Sybren; Apaydin, Hulya; Kiraz, Nuri
Abstract: Cladophialophora bantiana is a phaeoid fungus that only rarely has been isolated from sources other than the human brain. It has a particular tropism for the central nervous system (CNS). We have integrated and updated large-scale data related to several aspects of C. Bantiana and reviewed all the available reports on its cerebral infections, focusing on their geographical distribution, infection routes, immune status of infected individuals, type and location of infections, clinical manifestations and treatment and outcome, briefly looking over the spectrum of other disease entities associated with C. bantiana, that is, extra-cerebral and animal infections and on the environmental sources of this fungus. Among the agents of phaeohyphomycosis, a term used to describe an infection caused by a dark pigmented fungus, C. bantiana has some significant specific features. A total of 120 case reports were identified with a significantly higher percentage of healthy subjects than immune-debilitated patients (58.3% vs. 41.7%). Infections due to C. bantiana occur worldwide. The main clinical manifestations are brain abscess (97.5%), coinfection of brain tissue and meninges (14.2%) and meningitis alone (2.5%). Among immunocompetent patients, cerebral infection occurred in the absence of pulmonary lesions. The mortality rate is 65.0% regardless of the patient's immune status. The therapeutic options used include surgery or antifungals alone, and the combination of both, in most cases the fatal outcome being rapid after admission. Since the fungus is a true pathogen, laboratory workers should be made aware that BioSafety Level-3 precautions might be necessary.